Validity of Gamificaation Media for Cell Division Material to Improve Students Working Memory - Shofiana, Zanuba Laila; Prastiwi, Muji Sri (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2024)
The application of various curricula and the development of innovative learning models are also in the spotlight in this Industrial Revolution 4.0 era, especially in using learning media. Gamification, which involves game elements in learning, was introduced to increase student motivation and involvement. Working memory is a part of short-term memory that stores and manipulates information to help the learning process. This research aims to produce valid gamification media for cell division material to improve students' working memory. The type of research used in this research is development research using the ADDIE development model. Gamification media should meet specific criteria validated by material and education experts, including presentation, visuals, language, and content. The research showed that the gamification media for cell division material was declared high validity, with an average validation score of 0.94. Research has shown that gamification effectively enhances students' working memory as a learning tool. Keywords: validity, gamification media, cell division, working memory, education developing